"Three‐in‐one" patient‐specific surgical guides for simultaneous dental implants in fibula flap jaw reconstruction: A prospective case series. (12th November 2020) - Zhu, Wang‐yong; Su, Yu‐xiong; Pow, Edmond Ho Nang; Yang, Wei‐fa; Qin, Ling; Choi, Wing Shan
Abstract: Background: Conventional freehand immediate placement of dental implants is technically challenging in the jaw reconstructive surgery. Computer‐aided surgery might be the best solution, however, there has not been any standard approach to ensure the accuracy and efficiency of simultaneous dental implants in fibula flap jaw reconstruction. Purpose: We aim to evaluate the clinical outcome of simultaneous dental implant in fibula flap using the "three‐in‐one" patient‐specific surgical guide (3‐in‐1‐PSSG) in an open‐label, prospective, single‐arm, and single‐center clinical trial. Materials and Methods: A novel computer‐aided designed and three‐dimensional (3D) printed 3‐in‐1‐PSSG, which contains functions of fibula segmentation, surgical plate positioning and implant placement, was used to facilitate the reconstructive surgery and simultaneous dental implant placement. The intraoperative success of dental implant placement, implant survival rate and accuracy of dental implant placement were reported. Results: From November 2018 to June 2020, 15 consecutive patients with 48 dental implants were enrolled in this study. Fifteen 3‐in‐1‐PSSGs were fabricated with a mean number of dental implants per guide of 3.2 ± 1.5. The intraoperative success rate of this approach was 14 out of 15. With an average follow‐up period of 40 weeks, the overall implant survival rate was 83.3% (40/48). Eight implants were removed due to two fibula flap failures. The mean deviation at the implant platform and implant apex were 2.8 mm (interquartile range [IQR]: 1.9‐3.4) and 3.2 mm (IQR: 2.0‐4.6), and the angular deviation was 2.5° (IQR: 1.1‐6.8). Conclusions: Our preliminary data indicated that the 3D printed 3‐in‐1‐PSSG facilitated simultaneous dental implant in fibula flap jaw reconstruction with a favorable intraoperative success and short‐term clinical outcome. It might be a viable alternative to allow one‐step immediate oral rehabilitation in patients underwent jaw reconstruction with free flaps. Long‐term results with a larger sample size are warranted.